STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN MUTU LULUSAN DI MTS HASYIM ASY’ARI KOTA BATU - Muhammad Ilham Azzanjani; Rosichin Mansur; Mutiara Sari Dewi (VICRATINA, 2021)
For this reason, the head of the madrasa needs to prepare good strategies to improve the quality of its graduates so that they can achieve their goals optimally and can achieve the vision and mission of the madrasa in accordance with what was set from the start. In this study the researchers took the location at MTs Hasyim Asy'ari Batu City. An educational institution organized by the Al-Ma'arif foundation and administratively this has implications for the Ministry of Religion. MTs Hasyim Asy'ari Batu City is located on Jalan Semeru, Sisir District, Batu City. The position of the Madrasa which is located in the center of the city has resulted in many people who know this Madrasa. The research findings referred to here are data obtained from the results of field research that are in accordance with the problems contained in the focus of the problem in the previous chapter. After the data is collected using the method of observation, interviews and documentation, researchers can analyze the results of the study using data analysis techniques from Milles and Huberman which consist of data reduction, data presentation and verification. Thus, this research is a descriptive qualitative research, meaning that the researcher will describe, describe, and interpret the collected data so that they will obtain a general and comprehensive picture of the real thing.